Hemoglobin: A Nitric-Oxide Dioxygenase. (19th December 2012) - Gardner, Paul R.
Abstract : Members of the hemoglobin superfamily efficiently catalyze nitric-oxide dioxygenation, and when paired with native electron donors, function as NO dioxygenases (NODs). Indeed, the NOD function has emerged as a more common and ancient function than the well-known role in O2 transport-storage. Novel hemoglobins possessing a NOD function continue to be discovered in diverse life forms. Unique hemoglobin structures evolved, in part, for catalysis with different electron donors. The mechanism of NOD catalysis by representative single domain hemoglobins and multidomain flavohemoglobin occurs through a multistep mechanism involving O2 migration to the heme pocket, O2 binding-reduction, NO migration, radical-radical coupling, O-atom rearrangement, nitrate release, and heme iron re-reduction. Unraveling the physiological functions of multiple NODs with varying expression in organisms and the complexity of NO as both a poison and signaling molecule remain grand challenges for the NO field. NOD knockout organisms and cells expressing recombinant NODs are helping to advance our understanding of NO actions in microbial infection, plant senescence, cancer, mitochondrial function, iron metabolism, and tissue O2 homeostasis. NOD inhibitors are being pursued for therapeutic applications as antibiotics and antitumor agents. Transgenic NOD-expressing plants, fish, algae, and microbes are being developed for agriculture, aquaculture, and industry.